Sistematización de la intervención psicosocial para concientizar sobre las concepciones de feminidad y su relación con la violencia intrafamiliar, en mujeres que asisten al Centro de Equidad y Justicia del Valle de los Chillos en el periodo de abril a julio de 2017 - Conde León, Gabriela Marcela (2017)
This systematization was carried out with the purpose of investigating the conceptions that a group of women had about femininity and intra familial violence. These women had in common that all had been victims of violence, in some of its manifestations; In addition, they were receiving a beauty course at “Centro de Equidad y Justicia del Valle Los Chillos”. For this, ten workshops were held, in which, through different participation techniques, psychosocial intervention was developed. In these workshops spaces for dialogue and exchange were provided, in addition, they were given tools to identify and adequately combat violence, in all its manifestations. At the end of the workshops, a substantial change in the participants' conceptions of femininity and intra familial violence was evidenced, an empowerment of these women of their condition of being feminine, of the meaning of motherhood, and of the right they have of live without being violated. Regrettably, it cannot be said that the change has been profound or lasting, it is only an initial step to continue the work and to diminish (or eliminate) this serious problem of our society.